Cement concrete containing polyethylene terephthalate and steel slag powder for pavement application - Daniel Oguntayo; Oluwasegun Aladegboye; Hephzibah Otuene; Adekemi Balogun (Advances in Civil and Architectural Engineering)
The solid waste produced by industrial and technological advancements in the environment and construction is increasing. A large amount of industrial waste is not properly disposed of in Nigeria, which causes inconvenience to the environment and society. Utilising such waste for sustainable construction is one of the easiest and least expensive methods of eliminating and protecting the environment. This study investigated the properties of concrete pavement incorporating steel slag powder (SSp) and PET powder (PETp). The cement was partially replaced with SSp and PETp at varying proportions, and the mechanical properties (compressive strength, flexural strength, and split tensile strength) and durability properties (resistance to acid attack and water absorption) were evaluated for the concrete pavement. The results obtained indicate that the addition of SSp improved the strength characteristics of the concrete pavement, whereas the incorporation of PETp enhanced the durability performance. The findings suggest that the use of SSp and PETp in concrete pavements is a promising approach to achieving both mechanical strength and durability requirements because PETp replaces the water lost and prevents cracks from forming in concrete samples. Furthermore, to achieve best performance of the concrete pavement, the study recommends 10 % SSp and 15 % PETp as the ideal combination.